2011
DOI: 10.1007/s10549-011-1847-x
|View full text |Cite
|
Sign up to set email alerts
|

A plea for the biopsy marker: how, why and why not clipping after breast biopsy?

Abstract: In the last decade, percutaneous breast biopsies have become a standard for the management of breast diseases. Biopsy clips allow for precise lesion localization, thus minimizing the volume of breast to be resected at the time of surgery. With the development of many imaging techniques (including mammography, sonography, and breast magnetic resonance imaging), one of the challenges of the multidisciplinary became to synthesize all informations obtained from the various imaging procedures. The use of biopsy mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 59 publications
3
74
1
2
Order By: Relevance
“…Collagen (used in the MammoMARK™) has the added benefit of activating the coagulation cascade, which confers enhanced haemostasis. 2,4,17 One area of concern was that when the markers did displace in our study, the distance from the biopsy cavity was considerable -10 mm or more in 86% of the displaced cases. This is speculated to relate, at least in part, to the slippery surface of the gel-like polymeric component of some of the markers.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Collagen (used in the MammoMARK™) has the added benefit of activating the coagulation cascade, which confers enhanced haemostasis. 2,4,17 One area of concern was that when the markers did displace in our study, the distance from the biopsy cavity was considerable -10 mm or more in 86% of the displaced cases. This is speculated to relate, at least in part, to the slippery surface of the gel-like polymeric component of some of the markers.…”
Section: Discussionmentioning
confidence: 70%
“…In the early to mid-1990s, the placement of a radiopaque metallic post-biopsy clip began gaining popularity in cases where the mammographic abnormality was determined to be no longer visible. 2 Since then, the use of post-procedure markers after SVAB has become widespread, with most institutions, including ours, routinely placing the markers after all breast biopsies. Studies have shown that clear margins are obtained in 90-92% of excisional specimens when lesions are localized using biopsy markers vs 31-62% when wire localization is used alone.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations